Twitter as a tool to monitor attitudes: the strategic usage of social media - Villagrasa, Jorge; Donaldson, Colin; López Medina, Cortes (Journal of Management and Business Education, 2022)
This research delves into Twitter analysis, a well-known social media messaging service recently acquired by Elon Musk for 44bn, which we argue to enable researchers to better monitor (and try to solve) the status of the general population regarding the type of user and content of the received messages. With this analysis, it is intended to show the possibility of disseminating reliable, immediate, and high-quality messages (that would be unlikely obtained through official information channels), potentially provoking in this way an exponential impact afterwards. This idea in particular is key, due to any average social media population user and especially from 'Gen Z' (which hold 25% lower attention capacity and 40% lower check of the reliability of sources than its predecessor generation) could easily understand wrongly the massive (and unfiltered) amounts of information received, therefore generating false alarms, beliefs and in some cases, even own welfare losses. To do so, along this paper we propose the development of a pedagogical activity with a multi-methodological approach through which to carry out a qualitative (and cross-sectional) analysis in the degree of ‘Business Administration and Management’ of EDEM-Business School. Thus, the aforementioned activity would constitute a successful teaching innovation exercise as regards to the acquisition of the required competencies and learning outcomes established within the course, as well as to the achievement of a (attainable and consensual) solution to a real problem faced nowadays and selected by the students: in this case, the increase of awareness about the cervical cancer, a type of cancer that is currently the fourth most common among women worldwide and one of the easiest to prevent through screening tests.